Studi Kritis Dinamika Pendidikan Islam Bani Umaiyah Dan Peranannya Dalam Pendidikan Islam - Nurkhasanah, Ani Fitria; Zulmuqim; Fauza Masyudi (PT. Banjarese Pacific Indonesia, 2023)
The purpose of writing this research is to find out how Islamic education was during the Umayyad era and find out its role in the development of Islamic education. During the Umayyad dynasty, the education pattern was decentralized. Students who seek knowledge do not only study with one cleric, but go to other cities to continue and deepen their knowledge. The study of science in this period was centered in Damascus, Kufa, Mecca, Medina, Egypt, Cordova and several other cities, such as: Basrah and Kuffah (Iraq), Damascus and Palestine (Syam), Fustat (Egypt). The research method used is literature study by searching for relevant study material from trusted sources. The results of this research are the same as during the time of Rasulullah SAW and Khulafaur Rasyiddin. At this time, mosques and kuttabs are still used as educational institutions, apart from that, educational institutions have also developed. The role in the development of Islamic education is that Islamic education must be able to integrate reason and revelation to become a harmonious unity, the existence of student exchanges, translation of books or knowledge from foreign languages ​​to national languages, educational facilities in urban centers of government